Intestinal Preparation Techniques for Histological Analysis in the Mouse. Issue 2 (1st June 2016) - Williams, Jonathan M.; Duckworth, Carrie A.; Vowell, Kate; Burkitt, Michael D.; Pritchard, D. Mark
Abstract: The murine intestinal tract represents a difficult organ system to study due to its long convoluted tubular structure, narrow diameter, and delicate mucosa which undergoes rapid changes after sampling prior to fixation. These features do not make for easy histological analysis as rapid fixation in situ, or after simple removal without careful dissection, results in poor postfixation tissue handling and limited options for high quality histological sections. Collecting meaningful quantitative data by analysis of this tissue is further complicated by the anatomical changes in structure along its length. This article describes two methods of intestinal sampling at necropsy that allow systematic histological analysis of the entire intestinal tract, either through examination of cross sections (circumferences) by the gut bundling technique or longitudinal sections by the adapted Swiss roll technique, together with basic methods for data collection. © 2016 by John Wiley & Sons, Inc.